Analisis Yuridis Undang-Undang Penistaan Agama Dalam Hukum Islam - Rahmad Haniru; La Jidi; Abdul Nowi; Safaruddin Yahya (Departement of Mathematics Education, 2024)
This research aims to analyze the juridical law of deviant acts such as blasphemy against religion. It is important to pay attention, because religion is a sacred belief that should not be insulted or demeaned. Article 29 of the Constitution of the Republic of Indonesia states that